Spatio-temporal patterns of infectious disease vectors in the eastern Smoky Hills, Kansas - Ganser, Claudia (Kansas State University, 2012)
Nearly 30% of emerging infectious diseases are caused by vector-borne pathogens with wildlife origins, posing a risk for public health, livestock, and wildlife species of conservation concern. Understanding the spatial patterns of exposure to dipteran vectors and their associated pathogens is critical for epidemiological research to target prevention and control of vector-borne infectious diseases. In recent years, Western Equine encephalitis, St. Louis encephalitis, West Nile Virus encephalitis and avian malaria have not only been a public health concern but also a conservation concern, specifically the conservation of grassland nesting birds. Although the central Great Plains is the most specious region for grassland nesting birds, their role in the enzootic (primary) amplification cycle of infectious diseases may lead to further population depressions, and could potentially result in spill-over events to humans and livestock. The goals of my thesis were 1) to identify the underlying causes of spatio-temporal abundance patterns of mosquito vectors within the grasslands of the eastern Smoky Hills, and 2) to create probabilistic distributions of functional disease vectors, to evaluate disease risk in Greater Prairie-chicken (Tympanuchus cupido, surrogate species for other grassland nesting birds). First, I found that temporal dynamics in mosquito abundances were explained by maximum and minimum temperature indices. Spatial dynamics in mosquito abundances were best explained by environmental variables, such as curvature, TWI (Topographic Wetness Index), distance to woodland and distance to road. Second, the overall predictive power of the ecological niche models of important vector species in the grasslands of the Smoky Hills was better than random predictions, indicating that the most important predictor variables in their distribution were: distance to water, TWI, AASHTO (soil particle size distribution), and mean temperature during the coldest quarter. Furthermore, the spatial analysis indicated that Greater Prairie-chicken nest in areas with a higher probability of vector occurrence than other potentially available habitats within the grasslands. However, I failed to detect a significant difference in the probability of vector occurrence at nest of infected versus uninfected females. Understanding the distribution and abundance patterns of vectors of infectious diseases can provide important insights for wildlife conservation as well as public health management.
Keywords: Mosquito; West nile; Avian malaria; Meteorological variables; Topographic variables; Disease emergence; Biology (0306); Public Health (0573); Wildlife Conservation (0284)